Perencanaan Suksesi Dalam Bisnis Keluarga - Putri Wulansari; Rusnandari Retno Cahyani (JUMBIWIRA : Jurnal Manajemen Bisnis Kewirausahaan, 2024)
This research aims to discuss and determine the important role of family businesses in the Indonesian economy, with a focus on the characteristics, economic contribution and challenges faced by family businesses. There are unique characteristics of family businesses, such as the participation of family members, emotional strength, and complex problems faced. In addition, there is an emphasis on the importance of succession in the continuity of family businesses. A structured succession process is considered vital to ensure the continuity and improvement of family business performance. Other factors highlighted involve the performance of family firms, the influence of non-family leadership, and relationships between family members and the impact of education on the succession process. The research methodology uses a qualitative approach with literature studies, and the results show that succession planning has a significant positive impact on the success of family business succession. In addition, the involvement of family company founders, positive relationships from the family, and the influence of education on successor intentions are also important parts of the research conclusions.